The effect of mind mapping-based learning model on listening skills - Elisabet Janul (Curricula)
Several skills need to be mastered in the 21st century, one of which is communication. Good and correct communication will be formed if an individual masters four important language components. These components are listening, speaking, reading, and interrelated writing skills. This study tried to reveal the results of students' listening skills by using mind-mapping media during classroom learning. The approach used in this research is descriptive qualitative. The data collection techniques used in this research are observation, interview, and documentation. The subjects of this study were homeroom teachers and elementary school students. Data analysis techniques include data reduction, data display, and data verification. The research results show that using creative and innovative models can develop students' language skills. Learning media using mind-mapping media has improved students' listening skills. Of course, various efforts will continue to be made to create a 21st-century generation skilled in communicating properly and correctly.